Refractoriness to transarterial chemoembolization in patients with recurrent hepatocellular carcinoma after curative resection - Jeon, Mi Young (PLoS One, 2019)
BACKGROUND/AIMS: It is important to identify patients who are refractory to transarterial chemoembolization (TACE), which is performed for the treatment of hepatocellular carcinoma (HCC). We investigated the predictors of poor treatment outcomes in patients with recurrent HCC treated who were treated with TACE after curative resection. METHODS: 428 patients with recurrent HCC after curative resection who were treated with TACE were enrolled. RESULTS: The median age of the study population was 59.2 years. On multivariate analysis, ≥2 TACE procedures within 6 months (hazard ratio [HR] = 1.898), and the des-gamma carboxyprothrombin level (HR = 1.000) independently predicted the progression to Barcelona Clinic Liver Cancer (BCLC) stage C in patients with BCLC stage 0-B HCC (both P<0.05). In addition, ≥2 and ≥3 TACE procedures within 6 months independently predicted mortality in the entire study population (HR = 1.863 and 1.620, respectively). The probability of progression to BCLC stage C in patients with BCLC stage 0-B HCC and the mortality rate in the entire study population were significantly higher in patients treated with ≥2 TACE within 6 months than in those who underwent fewer procedures (P = 0.002 and P<0.001, respectively). CONCLUSIONS: More than 2 TACE procedures within 6 months might be associated with the refractoriness to TACE in patients with recurrent HCC after curative resection.